2013
DOI: 10.1101/gad.229559.113
|View full text |Cite
|
Sign up to set email alerts
|

Chromothripsis and beyond: rapid genome evolution from complex chromosomal rearrangements

Abstract: Recent genome sequencing studies have identified several classes of complex genomic rearrangements that appear to be derived from a single catastrophic event. These discoveries identify ways that genomes can be altered in single large jumps rather than by many incremental steps. Here we compare and contrast these phenomena and examine the evidence that they arise “all at once.” We consider the impact of massive chromosomal change for the development of diseases such as cancer and for evolution more generally. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
219
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(229 citation statements)
references
References 153 publications
(242 reference statements)
3
219
1
6
Order By: Relevance
“…The mechanisms underlying these differences are poorly understood. Chromothripsis is a possible mechanism to explain these genomic amplifications (28). Other multistep evolutionary process starting from single chromosome ancestral amplicons could explain the process (29).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying these differences are poorly understood. Chromothripsis is a possible mechanism to explain these genomic amplifications (28). Other multistep evolutionary process starting from single chromosome ancestral amplicons could explain the process (29).…”
Section: Discussionmentioning
confidence: 99%
“…The role of isolated structural variants in tumorigenesis is well studied (Forment et al 2012), but complete characterization of large-scale CGRs still present challenges that existing methods do not solve. In order to understand chromothripsis at a mechanistic level, Zhang et al (2013) recently demonstrated, using a combination of live cell imaging and single-cell genome sequencing, that micronucleus formation can indeed generate a spectrum of genomic rearrangements, some of which recapitulate all known features of chromothripsis. Recent reports have shown evidence for an independent cellular "path" to chromothripsis via telomere shortening and processing of the resulting dicentric chromosomes (Maciejowski et al 2015;Mardin et al 2015).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Chromoplexy, a phenomenon where complex genomic rearrangements typically involving up to 10 chromosomes is not uncommon, is known to occur extensively in prostate cancers (Baca et al 2013;Zhang et al 2013). We therefore looked at the distribution of contigs that span single, double, or multiple chromosomes For each of the identified contigs, we report their copy count, size, their type, and whether it was also identified by two other approaches.…”
Section: High Incidence Of Chromoplexy In Prostate and Bladder Cancersmentioning
confidence: 99%
“…Chromothripsis and chromoanasynthesis are two forms of genomic instability that lead to complex genomic rearrangements affecting one or very few chromosomes [1][2][3] . These two types of catastrophic events play a role in numerous tumor entities as well as in some congenital diseases 3,4 .…”
mentioning
confidence: 99%
“…4, 2018; 3 Chromothripsis and chromoanasynthesis are two forms of genomic instability that lead to complex genomic rearrangements affecting one or very few chromosomes [1][2][3] . These two types of catastrophic events play a role in numerous tumor entities as well as in some congenital diseases 3,4 . The first form, chromothripsis, is characterized by the simultaneous occurrence of tens to hundreds of clustered DNA double-strand breaks 1,5 .…”
mentioning
confidence: 99%